2010
DOI: 10.4081/ejh.2010.e4
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric evaluation of intestinal cellular immune responses in pigs immunized with live oral F4ac+ non-enterotoxigenic E. coli vaccine against postweaning colibacillosis

Abstract: Enterotoxigenic Escherichia coli (ETEC) infection is the most common type of porcine postweaning colibacillosis (PWC). Among fimbriae of porcine ETEC strains the best studied family of fimbriae are the members of F4 adhesins, existing in at least three variants: ab, ac, ad. Active immunization against porcine PWC is difficult due to: i) ETEC strains are only one of the essential predisposing factors, ii) the success of vaccinal antigen uptake depends on the presence of enterocyte receptors for F4 adhesins, iii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…The results obtained on the effectiveness of LEVA used as an immunomodulator to: (1) enhance proliferation of peripheral blood and intestinal immune cell subsets, (2) maintain gut health, and (3) improve productivity and performance of 4-wk-old weaned pigs based on the study during period of 5 wk postweaning were generally in agreement with many of our previous observations (Lackovic´et al 1997;Bozˇic´et al 2002aBozˇic´et al , b, 2003Bozˇic´et al , 2006Bozˇic´et al , 2011Janjatovic´et al 2008;Kovsˇca Janjatovic´et al 2010) and by others (Reyero et al 1979;Hennessy et al 1987;Kumar et al 1999;Bilandzˇic´et al 2010a, b). However, the study design and duration of our current research were rather different (i.e., immunization with a single dose of LEVA only, oral route of its application, age of pigs and considerably longer observation period), included measurements of more parameters (i.e., nutritional, bacteriological and immunological) than in similar studies Kovsˇca Janjatovic´et al 2009) and conveyed the pioneer data on influence of the drug on distribution and frequency patterns of naı¨ve lymphoid cells residing ileal mucosa of 9-wk-old pigs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results obtained on the effectiveness of LEVA used as an immunomodulator to: (1) enhance proliferation of peripheral blood and intestinal immune cell subsets, (2) maintain gut health, and (3) improve productivity and performance of 4-wk-old weaned pigs based on the study during period of 5 wk postweaning were generally in agreement with many of our previous observations (Lackovic´et al 1997;Bozˇic´et al 2002aBozˇic´et al , b, 2003Bozˇic´et al , 2006Bozˇic´et al , 2011Janjatovic´et al 2008;Kovsˇca Janjatovic´et al 2010) and by others (Reyero et al 1979;Hennessy et al 1987;Kumar et al 1999;Bilandzˇic´et al 2010a, b). However, the study design and duration of our current research were rather different (i.e., immunization with a single dose of LEVA only, oral route of its application, age of pigs and considerably longer observation period), included measurements of more parameters (i.e., nutritional, bacteriological and immunological) than in similar studies Kovsˇca Janjatovic´et al 2009) and conveyed the pioneer data on influence of the drug on distribution and frequency patterns of naı¨ve lymphoid cells residing ileal mucosa of 9-wk-old pigs.…”
Section: Discussionsupporting
confidence: 89%
“…More recently, we have observed that the drug, when given either alone or in combination with live oral F18ac ' non-ETEC vaccine, stimulated proliferation of the ileal CD21 ' B cells in 6-wk-old pigs (Kovsˇca Janjatovic´et al 2009). Also, the LEVA-adjuvanted live oral F4ac ' non-ETEC vaccine enhanced recruitment of CD45RA ' naı¨ve and CD45RC ' memory lymphoid cells, SWC3 ' macrophages and CD21 ' B cells residing in ileal mucosa of weaned pigs more strongly than did the vaccine alone (Kovsˇca Janjatovic´et al 2010). Pigs weaned at less than 3 wk of age have lower lymphocyte proliferative responses than pigs weaned at an greater age (Blecha et al 1983) and may have a reduced growth rate as a result of reduced immune protection (Bailey et al 1993).…”
mentioning
confidence: 93%
“…Recently, we have reported, based on the histomorphometric quantification of porcine intestinal immune cells, that it is possible to differentiate the responses of pigs immunized with levamisole-adjuvanted experimental mucosal vaccines against PWC from those of nonimmunized pigs. 10 , 11 Based upon these observations, we highlighted the query of whether and how the already recognized immunogenicity/adjuvanticity of levamisole 8 , 9 can influence de novo differentiation of the antigen-sampling M cells and consequently provide more feasible and effective immunization with mucosally delivered vaccines against enteric pathogens, such as porcine ETEC. In the case of positive answer, the study on development of an effective M cell-targeted vaccine against porcine PWC should be adjuvanted with levamisole in order to circumvent weak or tolerogenic responses.…”
Section: Resultsmentioning
confidence: 99%
“…The F4ac + E. coli strains used for either immunization or challenge infection were described in a previous study of our group. 11 Mouse IgG1 (clone C-04) monoclonal antibody (mAb), reactive with porcine cytokeratin peptide 18 16 was used as primary antibody (Biovendor Laboratory Medicine, Heildelberg, Germany). Polyclonal F(ab') 2 rabbit anti mouse IgG:HRP antibody (AbD Serotec, Oxford, UK) was used as secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation